Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Does $\operatorname{arcsec}(x) = 1 /\arccos(x)$? I have looked in a few books and Google'd it but I am not finding my answer.

share|cite|improve this question
Go to… and input log10(tan(x) + sec(x)) as your fuction. – Matthew Hoggan May 15 '14 at 21:53 – MattAllegro May 15 '14 at 21:53
Remember that arcsec delivers an angle as its value. Ordinarily, it makes no sense to take the reciprocal of an angle. – Lubin May 15 '14 at 22:58
up vote 2 down vote accepted

No. If you graph $\sec^{-1}(x) \cdot \cos^{-1}(x)$, you get:

-2 to 2 -15 to 15

You can clearly see that it isn't $1$.

share|cite|improve this answer

If $\sec^{-1} x = \theta$, then $x = \sec\theta$. This means $\frac1x = \cos\theta$, so $\cos^{-1}\frac1x = \theta$. So your equation is wrong; the correct statement is $$\boxed{\sec^{-1} x = \cos^{-1}\tfrac1x}$$

share|cite|improve this answer

Actually it's: $$\operatorname{arcsec}(x)=\arccos(1/x).$$

share|cite|improve this answer

No. It is not. If you look at the definitions

$$y=\frac{1}{\cos x}$$

and then we solve for the x

$$\frac{1}{y}=\cos x$$

$$\cos^{-1}\left(\frac{1}{y}\right) = x$$

and replace $x$ and $y$ to find the inverse


share|cite|improve this answer
Careful, $\cos^{-1}(\cos(x)) \neq x$ in some cases. – recursive recursion May 17 '14 at 18:49

Isn't. Draw $$\text{arcsec} x\arccos x$$

share|cite|improve this answer
Please avoid link only answers and add a plot if you are telling the OP to test his theory by graphing. – Cole Johnson May 16 '14 at 17:03

No, it is false. Probably you meant $\operatorname{arcsec}(x)=\arccos(1/x)$, which is true.

share|cite|improve this answer

It is straight forward, let $$\sec^{-1}(x)=\alpha$$ $$\implies \sec\alpha=x$$ $$\implies \frac{1}{\cos \alpha}=x$$$$\implies \cos \alpha=\frac{1}{x}$$ $$\implies \alpha=\cos^{-1}\left(\frac{1}{x}\right)$$ Substituting the value $\alpha=sec^{-1}(x)$, we get $$\bbox[4pt, border:1px solid blue;]{\color{red}{\sec^{-1}(x)=\cos^{-1}\left(\frac{1}{x}\right)}}$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.